Cyclohexane nitrosation to ϵ-caprolactam with high selectivity over HY supported transition metals and phosphotungstic acid catalysts. (October 2014) - Hao, F.; Liu, P.; You, K.; Luo, H.
Abstract : Transition metals and phosphotungstic acid were supported on HY by impregnation method. In addition, these prepared catalysts were used in the synthesis of ϵ-caprolactam from one-step nitrosation of cyclohexane in different reaction medium of oleum and concentrated sulphuric acid. Among these catalysts, the PW/HY gives better result of cyclohexane conversion of 9·9% and selectivity to ϵ-caprolactam of 75·9%. X-ray diffraction, Fourier transform infrared (FTIR), NH3 –temperature programmed desorption, pyridine FTIR, SEM, Brunauer–Emmett–Teller and N2 adsorption–desorption were used to characterise the HY and PW/HY. The characterisation results as well as the catalytic performance indicate that the increment of the Brønsted acid sites has positive effect on the cyclohexane nitrosation to ϵ-caprolactam. The catalysts play an important role in promoting nitrosyl sulphuric acid to form nitroso radical and further to obtain ϵ-caprolactam. In addition, a possible mechanism for liquid phase nitrosation of cyclohexane in different reaction medium was proposed.